Stability of Fluctating Baby-Skyrme Brane - Fadhilla Emir S.; Gunara Bobby E.; Suroso Agus; Atmaja Ardian N. (ITM Web of Conferences)
This work studies the stability of fluctuating Baby-Skyrme brane as a model for early-time cosmology recently introduced in [1]. The dynamical system consists of two dynamical quantities (ϕ, H) with two differential equations and one constraint. The solutions can be realized as a family of curves on a surface in ℝ3. We found that there exist stable solutions provided that the physical parameters (α, σ, k) satisfy certain conditions that are deduced from the linear stability conditions near the critical points.